β-Nicotinamide Mononucleotide Reduces Oxidative Stress and Improves Steroidogenesis in Granulosa Cells Associated with Sheep Prolificacy via Activating AMPK Pathway - Yu Cai; Hua Yang; Hui Xu; Shanglai Li; Bingru Zhao; Zhibo Wang; Xiaolei Yao; Feng Wang; Yanli Zhang (Antioxidants)
Oxidative stress is a significant factor in the death of granulosa cells (GCs), leading to follicular atresia and consequently limiting the number of dominant follicles that can mature and ovulate within each follicular wave. Follicular fluid contains a diverse array of metabolites that play crucial roles in regulating GCs’ proliferation and oocyte maturation, which are essential for follicle development and female fertility. However, the mechanisms behind metabolite heterogeneity and its effects on GCs’ function remain poorly understood. Here, we identified elevated nicotinamide levels in the follicular fluid of high-prolificacy sheep, correlated with oxidative stress in GCs, by an integrated analysis. In vitro experiments demonstrated that supplementation with β-nicotinamide mononucleotide (NMN) significantly increased the levels of nicotinamide adenine dinucleotide (NAD+) and adenosine triphosphate (ATP) in GCs. NMN treatment effectively reduced Lipopolysaccharide (LPS)-induced apoptosis and mitigated mitochondrial dysfunction, while also decreasing the production of reactive oxygen species (ROS), thereby enhancing the activity of the antioxidant defense system. Importantly, NMN treatment improved the impairments in steroid hormone levels induced by LPS. Mechanistically, the protective effects of NMN against GCs function were mediated via the AMPK/mTOR pathway. Collectively, our findings elucidate the metabolic characteristics associated with sheep prolificacy and demonstrate that NMN effectively protects GCs from LPS-induced dysfunction and enhances ovarian responsiveness via the AMPK/mTOR pathway. These findings also position NMN as a potential novel metabolic biomarker in enhancing ovarian function.